Orosomucoid proteins limit endoplasmic reticulum stress in plants - Wang, Ling‐Yan; Li, Jian; Gong, Benqiang; Wang, Rui‐Hua; Chen, Yi‐Li; Yin, Jian; Yang, Chang; Lin, Jia‐Ting; Liu, Hao‐Zhuo; Yang, Yubing; Li, Jianfeng; Li, Chunyu; et al. (The New phytologist, 2023)
Summary Sphingolipids are cell membrane components and signaling molecules that induce endoplasmic reticulum (ER) stress responses, but the underlying mechanism is unknown. Orosomucoid proteins (ORMs) negatively regulate serine palmitoyltransferase activity, thus helping maintain proper sphingolipid levels in humans, yeast, and plants. In this report, we explored the roles of ORMs in regulating ER stress in Arabidopsis thaliana. Loss of ORM1 and ORM2 function caused constitutive activation of the unfolded protein response (UPR), as did treatment with the ceramide synthase inhibitor Fumonisin B1 (FB1) or ceramides. FB1 treatment induced the transcription factor bZIP28 to relocate from the ER membrane to the nucleus. The transcription factor WRKY75 positively regulates the UPR and physically interacted with bZIP28. We also found that the orm mutants showed impaired ER‐associated degradation (ERAD), blocking the degradation of misfolded MILDEW RESISTANCE LOCUS‐O 12 (MLO‐12). ORM1 and ORM2 bind to EMS‐MUTAGENIZED BRI1 SUPPRESSOR 7 (EBS7), a plant‐specific component of the Arabidopsis ERAD complex, and regulate its stability. These data strongly suggest that ORMs in the ER membrane play vital roles in the UPR and ERAD pathways to prevent ER stress in Arabidopsis. Our results reveal that ORMs coordinate sphingolipid homeostasis with ER quality control and play a role in stress responses.